2002
DOI: 10.1096/fj.01-0720fje
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acids (CLAs) regulate the expression of key apoptotic genes in human breast cancer cells

Abstract: Conjugated linoleic acid (CLA) reduces mammary tumorigenesis in rodent models, induces apoptosis in rodent mammary tumor cell lines, and decreases expression of antiapoptotic bcl-2 in rat mammary tissue. This investigation focused on the cell mechanisms underlying the antitumor effects of CLA. Changes (mRNA, protein) in expression of major proapoptotic p53, p21WAF1/CIP1, bax, bcl-Xs genes, and the antiapoptotic bcl-2 gene were observed in malignant MCF-7 and MDA-MB-231 cells and in benign MCF-10a human mammary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
1
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 31 publications
6
43
1
2
Order By: Relevance
“…Importantly, our studies point to a critical role for Bcl-2 in mediating the apoptotic effects of CLA in TM4t cells. Previous Western blot studies indicated that t10,c12-CLA induced either a modest 20-25% loss, or no loss, of total cellular Bcl-2 protein in cultured colon, prostate or breast cancer cells [23,26,27]. However, using mitochondrial fractions, we found that t10,c12-CLA induced a marked concentrationdependent decrease of mitochondrial Bcl-2 after 3 days of treatment (10% of control levels relative to VDAC at 40 μM).…”
Section: Discussioncontrasting
confidence: 49%
“…Importantly, our studies point to a critical role for Bcl-2 in mediating the apoptotic effects of CLA in TM4t cells. Previous Western blot studies indicated that t10,c12-CLA induced either a modest 20-25% loss, or no loss, of total cellular Bcl-2 protein in cultured colon, prostate or breast cancer cells [23,26,27]. However, using mitochondrial fractions, we found that t10,c12-CLA induced a marked concentrationdependent decrease of mitochondrial Bcl-2 after 3 days of treatment (10% of control levels relative to VDAC at 40 μM).…”
Section: Discussioncontrasting
confidence: 49%
“…We also examined the effect of linoleic acid and conjugated linoleic acid on the proliferation of MCF-10A cells. Because Majumder et al (15) reported that conjugated linoleic acid could inhibit the proliferation of MCF-10A, a dose-response experiment was done. We found that under our cell culture conditions, the proliferation of MCF-10A cells was only slightly affected by either linoleic acid or conjugated linoleic acid.…”
Section: Resultsmentioning
confidence: 99%
“…MCF-10A cells have intact cell cycle checkpoint controls (33 -38), are aneuploid but have stable genomes comparable with human mammary epithelial cells (36), and have normal proliferation controls, including contact inhibition (31, 39 -43) and normal apoptotic machinery (37,38,44,45).…”
Section: Methodsmentioning
confidence: 99%